2022
DOI: 10.1038/s41391-022-00492-y
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase 2 study of bicalutamide with or without metformin for biochemical recurrence in overweight or obese prostate cancer patients (BIMET-1)

Abstract: Background: Metformin may have anticancer effects that are independent of its hypoglycemic effects. Retrospective studies have shown that metformin use is associated with decreased incidence of prostate cancer and prostate cancer-specific mortality. Preclinical studies suggesting additive anticancer effects of combining metformin and bicalutamide prompted this clinical trial ( NCT02614859 ). Methods: This open-label, randomized, phase 2 trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…A total of 16 RCTs reported on the change in BMI ( n = 2113 on MTF, n = 2252 on placebo/control, mean baseline BMI 25.7−35 kg/m 2 , MTF dose 500–2550 mg/day, intervention duration 3 months to 5 years). The pooled analysis showed an MD in change in BMI of −0.56 (95% CI −0.74, −0.37) kg/m 2 ( I 2 = 78%), favouring MTF 46,48,52,53,56,58,61,66,68,69,73,76,79,82–84 (Figure 3). Prespecified subgroup analysis did not show a significant difference according to the presence or absence of concomitant LSM, as a co‐intervention (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 16 RCTs reported on the change in BMI ( n = 2113 on MTF, n = 2252 on placebo/control, mean baseline BMI 25.7−35 kg/m 2 , MTF dose 500–2550 mg/day, intervention duration 3 months to 5 years). The pooled analysis showed an MD in change in BMI of −0.56 (95% CI −0.74, −0.37) kg/m 2 ( I 2 = 78%), favouring MTF 46,48,52,53,56,58,61,66,68,69,73,76,79,82–84 (Figure 3). Prespecified subgroup analysis did not show a significant difference according to the presence or absence of concomitant LSM, as a co‐intervention (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Clinical studies in metastatic, castration-resistant prostate cancer patients show that the addition of metformin is not able to rescue resistance to anti-androgen agent, abiraterone [ 30 ], nor is it able to improve survival or response outcomes when combined with a chemotherapy agent, docetaxel [ 31 ]. A recent trial combining metformin with a different anti-androgen agent, bicalutamide, in overweight and obese prostate cancer patients found that this paired treatment had no effect on PSA levels compared to bicalutamide alone [ 32 ].…”
Section: Metformin In Cancermentioning
confidence: 99%
“…Bicalutamide with or without metformin for biochemical recurrence in overweight or obese prostate cancer Patients (BIMET-1) [ 176 ]…”
Section: Metformin and Modulation Of The Immune Systemmentioning
confidence: 99%